The transition from vocational education and training to higher education: a successful pathway? - Hoelscher, Michael [Verfasser]; Hayward, Geoff [Verfasser]; Ertl, Hubert [Verfasser]; Dunbar-Goddet, Harriet [Verfasser] (My University, 2008)
"This paper questions whether participation in vocational education and training (VET) provides a successful progression route into UK higher education (HE). Following an overview of the UK policy agenda two inter-connected aspects of HE access are investigated: students' choice of institution and choice of subject. Analysis of administrative data shows that A-levels provide the major access route into more prestigious HE institutions. Students with VET backgrounds are more likely to start their HE studies at post-92 universities with lower RAE results. Different educational pathways also lead to different HE subject areas which, in turn, are connected to diverse labour market outcomes. Case study data identify highly individualised decision-making patterns for institutional and subject choice. Rational choice models can explain these choices only to a limited extent. Restrictive information strategies and other factors affecting individual choices require consideration and there are significant differences in motivational patterns between students regarding their choice of subject." (Autorenreferat, BIBB-Doku)
Keywords: G 2.5.3 Anschlussfähigkeit von Bildungsgängen; S 1.4 Hochschulbildung; I 2.2.1 Westeuropa; Durchlässigkeit im Bildungssystem; Hochschulzugang; Bildungsverlauf; Bildungsabschluss; Studienfachwahl; Großbritannien